EPISTEMOLOGI ILMU ASBAB AL-WURUD HADIS - Lestari, Lenni (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2015)
Apple-interchange-newline"> <!–EndFr–>This paper is supposed to explore the epistemology of sabab al-wurūd of hadith. The fial result are: First, asbāb al-wurūd is defied as a knowledge which pay attention to the causes of the emergence of an hadith and the condition around it. Second, the source of asbāb al-wurūd knowledge are books (read: creation) which related to the knowledge of asbāb al-wurūd. Third, the method to get asbāb al-wurūd is mainly trough narration (riwayat) and effort on judgment (ijtihad). Both last methods are divided into two, that are trough the narration of micro asbāb al-wurūd and trough the effort on judgment of macro asbāb al-wurūd. Every hadith has macro asbāb al-wurūd but not every one of it has micro asbāb al-wurūd. Fourth, asbāb al-wurūd, as a knowledge is a science focuses to the study of matn. Fifth, historically, asbāb al-wurūd didn’t have any contact to the philosophy of science, but based on truth theory, the one which is more appropriate to the process of asbāb al-wurūd’s validation is the coherence truth theory.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />